Stay or Go Back? Satisfaction and Motivations of Chinese Students Studying Abroad - Xinzhe , Xu (2023)
Introduction: The purpose of the study was to identify motivations for leaving and returning to the country of origin and satisfaction as factors associated with the decision-making to study abroad in a sample of Chinese students. The sample consisted of 190 Chinese students studying in western countries. A questionnaire was developed and administered. The answers to the questionnaire offered extensive information on the push & pull factors associated with the motivations to leave and return and satisfaction with the studies. The questionnaire also gathered sociodemographic information. The results provide a detailed understanding of the goals and needs of Chinese international students, conditioned by cultural, economic, educational, political, and equality factors. The main factors for Chinese students to decide whether to study abroad or return to China are cultural ones. The questionnaire may be of interest to universities and governments that wish to know the positive evaluations of the policies on the mobility of Chinese students abroad.